2013
DOI: 10.1590/s1415-790x2013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Aconselhamento sobre o teste rápido anti-HIV em parturientes

Abstract: Introduction: The pre and post-HIV test counseling is recommended by the Ministry of Health, and is a tool for reflection and joint decision-making. Objectives: To determine the proportion of women receiving counseling for submission to the HIV rapid test and to assess factors associated to not receiving counseling for this test. Method: A cross-sectional study was conducted in five "Baby-Friendly Hospitals" from the High Risk Pregnancy System in Rio de Janeiro City, Southeast Brazil. The study population were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
13

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
(14 reference statements)
1
3
0
13
Order By: Relevance
“…The authors found that there was a greater chance of not receiving counseling among low-income pregnant women and who initiated prenatal tests belatedly. Similar results were reported by Passos et al 8 in a study of 955 mothers in a collective housing who had done rapid HIV tests in which only 26.9% received counseling. There was a significant association between lack of counseling and lower education of mothers(less than eight years of study) and the low number of prenatal visits.…”
Section: Hivtest Advice and Ethical Aspectssupporting
confidence: 88%
“…The authors found that there was a greater chance of not receiving counseling among low-income pregnant women and who initiated prenatal tests belatedly. Similar results were reported by Passos et al 8 in a study of 955 mothers in a collective housing who had done rapid HIV tests in which only 26.9% received counseling. There was a significant association between lack of counseling and lower education of mothers(less than eight years of study) and the low number of prenatal visits.…”
Section: Hivtest Advice and Ethical Aspectssupporting
confidence: 88%
“…This inconsistency suggests the occurrence of incomplete records 24 and possible flaws in the counseling of mothers by the health staff 25 . The Ministry of Health recommends that women be consulted if they want to undergo rapid HIV testing through counseling 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Health recommends that women be consulted if they want to undergo rapid HIV testing through counseling 4 . By reason of the greater proportion of women tested identified in the medical records in relation to the interviews, many participants were probably not even informed of the submission to the test, which impairs women's autonomy and guidance on HIV and vertical transmission prevention 25 . We can conclude that the ministerial protocols for HIV testing during pregnancy and hospitalization in force at the time of the study 3,4 were not followed to satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…O teste mais rápido dá o resultado em 30 minutos (PASSOS et al, 2013). Entretanto, o teste rápido tem sido empregado para precaução da transmissão vertical na ação de parto, em populações nomeadas de difícil acesso, como os usuários de drogas injetáveis e profissionais do sexo.…”
Section: Conceituando O Hivunclassified